Sistem Pengangkatan Anak Ditinjau Berdasarkan Hukum Positif dan Hukum Islam di Indonesia - K, Kefianto; Akbar, Agil Masyhur; Sakti, Muthia (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Adoption of children can be from anywhere, whether it is a child from a family, a child from another person, or a child in an orphanage. Child adoption in Indonesia is permitted and approved with good intentions as stated in Government Regulation Number 54 of 2007 and Law Number 23 of 2002 concerning Child Protection and meets the requirements. Indonesia itself does not have regulations regarding child adoption in the Burgerlijk Wetboek or Civil Code (KUHP). The research method in this study uses qualitative research methods. Qualitative research is a research method with the aim of understanding a phenomenon about what is experienced by research subjects or phenomena that occur in society. In this qualitative research process, a statutory approach is also used. Based on the research results, it was found that in Indonesia, in general, there are two ways to adopt a child, namely through a civil law perspective and using an Islamic legal perspective, both of which have been recognized by statutory regulations. There are several similarities between adoption of children both according to civil law and Islamic law, namely that adoption must be carried out through a legal process (through a district court or religious court) while the difference is that according to civil law adopted children can get inheritance rights whereas according to Islamic law adopted children does not receive inheritance rights from the parents who adopted him.